2008
DOI: 10.1007/s12011-008-8193-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Migraine with and Without Aura

Abstract: Migraine is the most common neurological disorder, but the molecular basis is still not completely understood. An impairment of mitochondrial oxidative metabolism might play a role in the pathophysiology. The goal of this study was to investigate the differences in oxidative stress status with the measurement of erythrocyte superoxide dismutase (SOD), catalase activity, and malondialdehyde (MDA) levels in the migraine patients with or without aura and attack. There were 56 patients (46 female, 10 male) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 22 publications
4
80
0
Order By: Relevance
“…A low concentration of platelet SOD levels and a decreased SOD activity in MwA have been reported, suggesting a higher vulnerability to oxidative stress in these patients (7). Higher SOD activity in red cells in patients with MwA compared with those with MwoA, probably due to a relative increase in oxidative stress due to vasoconstriction induced by ROS and associated with occurrence of aura, has also been described (8). Conversely, no changes in SOD concentration in neutrophils and platelets of MwA patients have been described (2), and a not considerable decrease in erythrocytes from 34 young patients suffering from MwoA or MwA was found (2).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A low concentration of platelet SOD levels and a decreased SOD activity in MwA have been reported, suggesting a higher vulnerability to oxidative stress in these patients (7). Higher SOD activity in red cells in patients with MwA compared with those with MwoA, probably due to a relative increase in oxidative stress due to vasoconstriction induced by ROS and associated with occurrence of aura, has also been described (8). Conversely, no changes in SOD concentration in neutrophils and platelets of MwA patients have been described (2), and a not considerable decrease in erythrocytes from 34 young patients suffering from MwoA or MwA was found (2).…”
Section: Resultsmentioning
confidence: 91%
“…Increased oxidative stress is a key event in migraine physiopathology (2,7,8), and generation of diffusible reactive oxygen species (ROS) in the cerebral cortex activates nociceptive transmission during the attack in migraine with aura (MwA) (6). Therefore, antioxidants and ROS scavengers have been suggested as promising therapeutic strategy for migraine (6).…”
mentioning
confidence: 99%
“…Malonyl aldehyde (MDA) is a major indicator of lipid peroxidation and determines the activities of antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (Glut-px), glutathione reductase (GSSG-R), and catalase (CAT). Studies have shown the lipid peroxidation and levels of these antioxidant enzymes in migraine patients [19][20][21][22][23]. Conversely, studies of this type are few and their results are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Thiobarbituric acid-reactive substances (TBARS), oxidative stress markers, have been found increased in plasma [24] and 24-h urine [3,4] of patients with migraine in headache-free periods, and urinary excretion was even more increased during migraine attacks [3]. Malonildialdehyde (MDA), a marker of lipid peroxidation, has been found increased [25,26] or decreased [2] in erythrocytes, and decreased in serum [2]. Cu/Zn-superoxide-dismutase (Cu/Zn-SOD) concentrations have been found normal in platelets of patients with migraine [2,21,25] while platelet Cu/Zn-SOD activity has only been found decreased in migraine with aura [21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Malonildialdehyde (MDA), a marker of lipid peroxidation, has been found increased [25,26] or decreased [2] in erythrocytes, and decreased in serum [2]. Cu/Zn-superoxide-dismutase (Cu/Zn-SOD) concentrations have been found normal in platelets of patients with migraine [2,21,25] while platelet Cu/Zn-SOD activity has only been found decreased in migraine with aura [21,25]. Total SOD activity has been found normal [2] or decreased [5] in serum, and normal in platelets [22] and in neutrophils [22].…”
Section: Introductionmentioning
confidence: 99%